PENDIDIKAN SEKS DALAM ISLAM; Suatu Upaya Pembebasan Tindak Kekerasan Seksual Remaja - Wahyudi, Arif (KARSA: Journal of Social and Islamic Culture)
AbstractIn Indonesia, public regard sex as something natural. Sex is godâ€™s omnipotence, hence it is not important to communicate it to children and teenagers. They will know the information about sex as soon as they grow older. However the rapid growth of mass media, puts many parents in a dilema. How the parents protect the children from the trapÂ  of cultural sexuality values, and social reality values particularly from the case of sexual harshment. One of the ways to protect them is by socializing sex education earlierly. It is to let the teenagers have sufficient knowledge of sex. Kata-kata kunciremaja, pendidikan seks, kekerasan seksual